Multiparty quantum communication protocol based on quantum stabilizer codes with identity authentication. (23rd March 2021) - Li, J. X.; He, Z. X.; Zhao, S.; Yan, D. D.; Ma, H. Y.
Abstract: Quantum communication has been extensively studied and continuously developed due to its theoretical absolute security. In this work, a novel multiparty quantum communication protocol based on quantum stabilizer codes (QSC) is proposed. Firstly, a trusted third party provides quantum identity authentication (QIA) for users. Secondly, users prepare quantum multiparticle entangled states for transmitting secret information. Thirdly, the secret information is encoded by the QSC to resist channel noise. A part of the encoded qubits is selected to detect the security of the communication. In this protocol, QIA prevents active attacks such as impersonation attacks; the physical laws of quantum entangled state ensure information security; the theory of QSC corrects the flipping errors of qubits, and improves the communication efficiency. In addition, we prove the security of the protocol, and further verify the communication efficiency. Compared with existing protocols, this protocol has better performance on communication efficiency.